Pelatihan dan Pendampingan Manajemen Usaha Kerajinan Limbah Batu Padas di Kabupaten Badung Bali - Ni Made Satya Utami; Yenny Verawati; Putu Novia Hapsari Ardianti; Pande Ketut Ribek; I Made Purba Astakoni (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
Local handicrafts Bali got a lot of challenges and competitors from outside the region so that the SMEs are required creativity to create the product design, improve the production process, quality, coloring products, and it remains to accentuate the local wisdom, to attract the tastes of consumers and is one of the efforts to increase sales and be able to compete outside the region. The purpose of devotion is doing the arrangement layout of the production process, improve the quality, design, staining, burning products to be ready for export, as well as perform administrative bookkeeping simple, to improve the welfare of the SME Partners so that businesses can be sustainable. A method of devotion through this approach: (1) socialization and arrangement of means of layout, (2) training and mentoring, (3) monitoring and evaluation. The results of the devotion of the SME Partners have layouts work better so the shelves and the process of production has separate, business management simple bookkeeping made regular and periodic, can create a design attractive product with painting techniques and burning can cause the effect of the product a memorable vintage. The evaluation is done as an input for the improvement of activities of that kind of next. Conclusion SMEs can improve product quality and accelerate the production process, the enrichment of the field of coloring and combustion products to realize the variety and quality of the product increased.